2001
DOI: 10.1002/1097-4652(2000)9999:999<000::aid-jcp1040>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

17-B estradiol elicits an autocrine leiomyoma cell proliferation: Evidence for a stimulation of protein kinase-dependent pathway

Abstract: The mechanism by which estradiol (E2) acts on cell proliferation is still unclear. In this paper, we report the results of a series of experiments in an attempt to elucidate the effector pathway(s) involved in coupling the E2 receptors binding to cellular growth response in leiomyoma cells (LSMC). Under conditions of E2-dependent growth, E2 treatment of LSMC triggers rapid and transient activation of the MAP-kinase pathway. Interestingly, we demonstrate that the early downstream signal transduction events dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 32 publications
1
47
1
5
Order By: Relevance
“…We chose to comment on PTN in this article because of its unique overexpression in our array, several reports that describe up-regulation of angiogenesis-related growth factors in leiomyoma (25,26), new advances in tumor biology, and the recognition that PTN is a growth factor that is elevated in tumor cells (27)(28)(29). Tumorigenesis is complex and is regulated in part by cellular phenotype growth, invasion, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to comment on PTN in this article because of its unique overexpression in our array, several reports that describe up-regulation of angiogenesis-related growth factors in leiomyoma (25,26), new advances in tumor biology, and the recognition that PTN is a growth factor that is elevated in tumor cells (27)(28)(29). Tumorigenesis is complex and is regulated in part by cellular phenotype growth, invasion, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence emphasize that this biologic mechanism is locally mediated by some growth factors [27][28][29][30][31] that, acting in an autocrine or paracrine manner, stimulate myoma growth mainly by mitogenic and angiogenic effects. A local deregulation of vasoactive growth factors or of their receptors has been hypothesized in the myomatous uterus [32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Barbarisi and colleagues demonstrated that E 2 treatment for 1, 5 and 30 min triggers rapid activation of phosphatidylinositide 3-kinases (PI3K), mitogen-activated protein kinase (MAPK) and phosphoinositide phospholipase Cγ (PLCγ) (32). In addition, Nierth-Simpson and colleagues (33) showed that E 2 treatment for 5 min activates protein kinase Cα (PKCα) in both human leiomyoma cells and human smooth muscle cells.…”
Section: Steroid Signaling Estrogenmentioning
confidence: 99%